CONSUMER SATISFACTION ONLINE OJEK SERVICES IN INDONESIA :EFFECT OF SERVICE QUALITY AND CUSTOMER VALUE - Maftuchah, Viniyati; Ghofir, Ade; ., Sabil; Riftiasari, Dinar (Archives of Business Research, 2019)
The shift of the use of conventional transportation to online transportation networks has resulted in a decrease in the market share of conventional transportation. The design of this study is causal research, which explains causal relationships between research variables to determine the causal relationship pattern of the independent variables on the dependent variable. The variables in this study are the service quality of the independent variable, customer satisfaction of the dependent variable, and the value of the customer intervening variable. Samples obtained by 100 respondents and taken by Purposive Sampling. The number of samples in this study was determined by the SEM analysis method where the number of indicators multiplied by five. Analysis of the data used is SmartPLS version 3.2. The results showed that all hypotheses could be accepted, where service quality had a positive and significant effect on customer value, but the effect of service quality on customer satisfaction had positive but not significant results, customer value had a positive and significant effect on customer satisfaction and service quality had a positive and significant effect to customer satisfaction through customer value.